2019
DOI: 10.1007/s00401-019-02023-x
|View full text |Cite
|
Sign up to set email alerts
|

Depopulation of dense α-synuclein aggregates is associated with rescue of dopamine neuron dysfunction and death in a new Parkinson’s disease model

Abstract: Parkinson’s disease (PD) is characterized by the presence of α-synuclein aggregates known as Lewy bodies and Lewy neurites, whose formation is linked to disease development. The causal relation between α-synuclein aggregates and PD is not well understood. We generated a new transgenic mouse line (MI2) expressing human, aggregation-prone truncated 1–120 α-synuclein under the control of the tyrosine hydroxylase promoter. MI2 mice exhibit progressive aggregation of α-synuclein in dopaminergic neurons of the subst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
89
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 37 publications
8
89
1
1
Order By: Relevance
“…Using simple, yet powerful, human cell-based models, we found that anle138b reduces aSyn aggregation in a HEK293 venus BiFC cell model. Until now, anle138b was mostly tested in mouse models 18,23,47 . In cells, it was tested in melanoma and in H4 cells 24, 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Using simple, yet powerful, human cell-based models, we found that anle138b reduces aSyn aggregation in a HEK293 venus BiFC cell model. Until now, anle138b was mostly tested in mouse models 18,23,47 . In cells, it was tested in melanoma and in H4 cells 24, 48 .…”
Section: Discussionmentioning
confidence: 99%
“…The deposition of fibrillary α‐syn is believed to start from synaptic terminals and can damage neurons via a two‐hit mechanism. This involves loss of function of α‐syn and collapse of synapses deriving from insoluble aggregates accumulation . The removal of α‐syn aggregates could thus reduce the neurotoxic effects of fibrils and also slow down prion‐like propagation of pathology.…”
Section: The Possible Approaches To Directly Target α‐Syn Pathologymentioning
confidence: 99%
“…NPT100‐18A was designed to target membrane‐bound α‐syn and to counteract oligomerization, while NPT200‐11 was optimized to bind specific regions of α‐syn thought to be responsible oligomerization into toxic forms and also to be orally bioavailable and brain penetrating . Finally, Anle138b, a small compound with high bioavailability and low toxicity, decreases α‐syn oligomerization and aggregation and reduces motor impairment and degeneration in MSA and PD mouse models . Of note, Anle138b is one of the few compounds successfully tested in vivo, since most of the molecules mentioned above have been tested on different cell lines or even in cell‐free models of α‐syn fibrillation (all the compounds mentioned are summarized in Table ).…”
Section: The Possible Approaches To Directly Target α‐Syn Pathologymentioning
confidence: 99%
See 2 more Smart Citations